The Effectiveness of The Food Supply and Price Stabilization Rice Policy on The Rice Market in East Java - Rachmadhan, Aditya Arief; Wijayati, Prasmita Dian (Journal of Agri-Food Science and Technology, 2025)
Rice has become a central focus of the Indonesian government in ensuring both availability and price stability. To address these concerns, the government, through Perum Bulog, introduced the SPHP (Stabilization of Food Supply and Prices) rice policy. This study aims to analyze the effectiveness of SPHP rice policy in influencing the price of premium rice in East Java Province. This study contributes to the limited empirical evidence on food policy evaluation in Indonesia and offers insights for designing more differentiated price stabilization strategies. The analysis in this study was conducted using a fixed effect model–dynamic unbalanced panel data regression with a double-log natural functional form. The dataset consists of monthly panel data covering 34 cities/regencies in East Java Province over the period June 2024–May 2025. The estimation results indicate that only the lagged premium rice price has a significant effect on the premium rice price. However, the price of SPHP rice, both current and lagged, does not have a significant effect on the price of premium rice.